Overview of Methods for Purification and Characterization of Metalloproteins. Issue 8 (26th August 2021) - Harnden, Kevin A.; Roy, Anindya; Hosseinzadeh, Parisa
Abstract: Metalloproteins make up one third of all proteins and perform some of the most essential reactions on earth. The unique properties of the metal ions within these proteins, and in particular of redox‐active metal ions, enables the use of a number of characterization techniques. It also necessitates unique considerations in terms of purification and characterization. In this overview, we describe the considerations and methods used for metalloprotein purification and characterization. © 2021 Wiley Periodicals LLC.